Representing Electrons : a Biographical Approach to Theoretical Entities. - Arabatzis, Theodore, 1965- (University of Chicago Press, 2011)
Both a history and a metahistory, Representing Electrons focuses on the development of various theoretical representations of electrons from the late 1890s to 1925 and the methodological problems associated with writing about unobservable scientific entities. Using the electron--or rather its representation--as a historical actor, Theodore Arabatzis illustrates the emergence and gradual consolidation of its representation in physics, its career throughout old quantum theory, and its appropriation and reinterpretation by chemists. As Arabatzis develops this novel biographical approach, he portray.